Data from air, englacial and permafrost temperature measurements on Mt. Ortles (Eastern European Alps) - Carturan, Luca; De Blasi, Fabrizio; Dinale, Roberto; Dragà, Gianfranco; Gabrielli, Paolo; Mair, Volkmar; Seppi, Roberto; Tonidandel, David; Zanoner, Thomas; Zendrini, Tiziana Lazzarina; Dalla Fontana, Giancarlo (Zenodo, 2023)
The *.xlsx files report the temperature data recorded between 2010 and 2016 and presented in the paper “ Modern air, englacial and permafrost temperatures at high altitude on Mt. Ortles, (3905 m a.s.l.) in the Eastern European Alps ” (Carturan et al., 2023, submitted). The data were used to display the time series reported in the paper, which details variable names, data quality flags, maintenance logs of field operations, and characteristics of measurement sites. The data files are the following: Ortles_Air_temperature.xlsx : includes the air temperature data measured by five sensors installed on an automatic weather station. Ortles_englacial_temperature.xlsx : includes the englacial temperature measured at different depths by four thermistor strings. Ortles_soilsurface_temperature.xlsx : includes the soil surface temperature measured at six different locations over deglaciated terrain. Ortles_rockwall_temperature.xlsx : includes the rockwal temperature measured at three different depths and six different locations. Each *.xlsx file contains the following fields: “ Date and hour (UTC) ”: format day/month/year hour:minute; “ Variable name (depth m) ”: name of the measured variable and the sensor depth (if applicable); “ Quality flag code ”: a code reporting data quality; Different spreadsheet report temperature data from different measurement sites. This dataset was collected in the framework of the Ortles Project (a program supported by two NSF awards no. 1060115 & no. 1461422 to The Ohio State University and by the Ripartizione Protezione Antincendi e Civile of the Autonomous province of Bolzano in collaboration with the Ripartizione Opere idrauliche e Ripartizione Foreste of the Autonomous province of Bolzano and the Stelvio National Park) and of the Italian MIUR Project (PRIN 2010-11), "Response of morphoclimatic system dynamics to global changes and related geomorphological hazards" (local and national coordinators G. Dalla Fontana and C. Baroni).